Sustainability of shallot farming system in lowland Central Java Province, Indonesia: MICMAC analysis approach - Dewi Sahara; Umi Karomah Yaumidin; Tota Suhendrata; Cahyati Setiani; Jajuk Aneka Beti; Triyani Dewi; Andi Yulyani Fadwiwati; Idaryani; Atman; Yardha; Edwen Waas; Robet Asnawi; et al. (Environmental Challenges, 2025)
Shallot farming in Central Java thrives in lowlands due to faster harvests and higher productivity. However, its sustainability faces climate change, water scarcity, pests, price fluctuations, and limited resources and technology. This study aims to determine the key factors for the sustainability of the shallot farming system in the lowlands of Central Java Province. The study was conducted in Brebes Regency with 21 respondents, Demak (38 respondents), Pati (32 respondents), and Grobogan (20 respondents). Primary data obtained using survey methods, in-depth interviews, and Focus Group Discussion (FGD) from 111 shallot farmers were used for data analysis. The data analysis method used structural analysis of the Matrix of Cross Impact Multiplication Applied to a Classification (MICMAC). The results showed that there were 16 variables from four dimensions: environment, economy, society, and technology. The analysis results show that knowledge, culture, and weather are key factors that directly determine the sustainability of the shallot farming system in the lowlands of Central Java Province; the weather shifts from quadrant I to quadrant II, indicating long-term instability. The variables of pest and disease control, water availability, and productivity show a strong indirect relationship between variables. This condition shows the importance of adjusting long-term strategies to face changes for the sustainability of shallot farming. Smart farming technology (drip irrigation, superior varieties, and integrated pest management), as well as increasing farmer knowledge and culture, are innovative steps for the sustainability of the shallot farming system in the lowlands of Central Java Province.